Guidebook on Capital Investment Planning for Local Governments - Kaganova, Olga (World Bank, Washington, DC, 2014)
The purpose of this guidebook is to provide practical advice to local governments (LGs) in developing countries on how to establish and maintain a process of planning and funding capital investment as a regular activity integrated with other activities of the LG and based on principles of good public management. The guidebook is addressed mainly to cities that have not yet established such a process or are interested in revising their current processes. The guidebook is written for decision makers and technical experts in LGs who are engaged or should be engaged in this process. The guidebook is designed primarily for urban LGs, but much of the information is useful for mixed or rural jurisdictions as well. This guidebook also is useful for the staffs of donor agencies and/or consultants who assist cities in municipal development projects. This guidebook is one instrument integrated with other World Bank urban programs and instruments that support sustainable urban development in developing countries within the framework of the World Bank Urban and Local Government Strategy. These other urban programs include the: (1) Urbanization Review Framework (URF), which provides macro-level diagnostic tools to identify key policy issues related to urbanization and the investment priorities for it; (2) Eco2: Ecological Cities as Economic Cities (city or metropolitan sustainable urban development initiative that assists developing country cities to achieve environmental and economic sustainability; and (3) Disaster Risk Management Program (DRM). This guidebook will help LGs prepare specific capital investment plans (CIPs) based on their national urbanization strategies and city-based sustainable urban development plans elaborated through the Eco2 initiative and/or various Disaster Risk Management Program (DRM) instruments. The guidebook will be especially useful to LGs if they have adopted their urbanization strategies and established clear investment priorities.